Altered Default Mode Network Functional Connectivity in Parkinson’s Disease: A Resting-State Functional Magnetic Resonance Imaging Study - Chen, Lu; Huang, Ting; Ma, Di; Chen, Yu-Chen (Frontiers in Neuroscience, 2022)
Purpose: Whether intrinsic functional connectivity pattern of default mode network (DMN) involves in the progression of cognitive decline in Parkinson's disease (PD) remains unclear. The current study aimed to investigate the intrinsic functional connectivity (FC) pattern of the DMN anchored on posterior cingulate cortex (PCC) in PD patients using resting-state functional magnetic resonance imaging (fMRI). Methods: Fifty PD patients and 50 healthy controls (HCs) were included for resting-state fMRI scanning. A seed based FC method was conducted to reveal FC patterns within the DMN with region of interest in the PCC. The relationships between FC patterns and disease severity (UPDRS-III) were detected. Results: Compared with HCs, PD patients showed increased FC between the PCC and the right precuneus, left cuneus and right angular gyrus. In the PD group, the increased FC values in the right precuneus were significantly positively correlated with motor severity as assessed by UPDRS-III scores (rho = 0.337, p = 0.020). Conclusion: Our result highlights that PD patients showed increased FC between the PCC and the right precuneus, left cuneus and right angular gyrus within DMN. Altered connectivity pattern within the DMN may play a crucial role in neurophysiological mechanism of cognitive decline in PD patients. These findings might provide new insights into neural mechanisms of cognitive decline in PD.